MiniCex as an Assessment Tool of a Medical Course Internship Program - Oliveira,Céres Larissa Barbosa de (2020)
Abstract: Introduction: Program assessment is the process of data collection about a course or teaching program that takes into consideration the aspects of cost-effectiveness, checking the adequacy of the evaluation according to the course purpose and the program capacity to yield changes in real life. Such regular assessments provide feedback to the decision-making process that aim at better teaching and learning practices. The Mini Clinical Evaluation Exercise (MiniCex) is a performance rating scale designed to assess the skills that medical students and residents need in real-life situations with patients. Considering the importance of program assessment for an institution, the utilization of the MiniCex data might be of great value for the follow-up of students and the course, helping the planning process and generating improvements in the institution. Therefore, the objective of this study is to assess the program using MiniCex in the beginning of the medical internship, aiming to determine in what areas of the basic and pre-clinical course the students have more difficulties. Methods: A cross-sectional descriptive study was carried out, using the retrospective data obtained by the MiniCex forms that were applied to the 9th-semester medical students, which correspond to the first semester of medical internship in the Federal University of Pará. A total of 111 students was assessed, among the 154 students eligible for internship, from August 2017 to July 2018. Results: Among the performed evaluations, with 97% being requested by the teachers, most of them (72%) were about new cases, and 45% and 38% had low or moderate complexity, respectively. There was a predominance of musculoskeletal system disorders (27.7%), followed by the gastrointestinal/hepatology system (14.8%). Concerning the skills in each domain, the performance was satisfactory in all of them. We observed that 12% of the students had difficulties in at least one area, followed by 6.3% of students with difficulties in 2 areas and 4.5% with an unsatisfactory performance in 3 or more areas. Conclusion: the MiniCex, when applied to internship students, showed to be a source of important and useful information, as part of a program assessment concerning the areas preceding the internship. The analysis of the obtained data was sent to teachers of the pre-internship, internship and course management areas. To the first ones, with the objective of reviewing their programs, detecting where they can intervene and, thus, make changes that aim a better acquisition of basic knowledge by the students and, consequently, improve their performance. To the second ones, to provide an overview of where they will have to focus their programs according to the needs of the medical students who reach the internship. Finally, to the course management, as a guide of what should be supervised by the professionals teaching the semesters that precede the internship.